Corporate Governance And Leverage : Study Of The Financial Sub-Sector Of State-Owned Companies And Regional-Owned Companies Performance - Muhamad Muslih; Gita Berliana Febrianti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The operations of the company, which are essential to its success through enhancing shareholder welfare, produce the performance of the company. Businesses seek to make money and enhance performance, but remain individualistic from internal and external parties in a company. This study can serve as a springboard for further research on the simultaneous and partial effects of independent board of commissioners institutional ownership, managerial ownership and leverage on company performance. State-owned companies and regional-owned companies segments that are listed on the indonesia stock exchange for the years 2014-2021 period are used in this research. This study used panel data regression analysis method. Six state-owned and regional-owned companies in the financial subsector that are listed on the IDX for the 2014–2021 period are selected as the sample utilizing the purposive sampling method, providing 48 data. The data sources used are secondary data in the form of annual reports and company financial statements. In the data analysis method, the author uses descriptive analysis with EViews software version 12. The results of this study explain that the independent board of commissioners, institutional ownership, managerial ownership and leverage have a significant effect simultaneously on the company's performance which is proxied by Return On Asset (ROA), independent board of commissioners, institutional ownership and leverage do not have a significant effect on company performance and on managerial ownership variables have a significant influence on company performance.